2017
DOI: 10.1186/s41182-017-0064-7
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of bronchiolitis: a description of emergency department visits and hospitalizations in Puerto Rico, 2010–2014

Abstract: BackgroundLittle is known about the epidemiology of bronchiolitis as a clinical diagnosis and its impact on emergency department visits and hospitalizations in tropical and semitropical regions. We described the epidemiology of bronchiolitis emergency visits and hospitalizations, its temporal trend and geographic distribution in Puerto Rico between 2010 and 2014.MethodsWe performed a retrospective descriptive analysis of a representative sample of privately insured children with bronchiolitis from January 2010… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 41 publications
0
11
0
3
Order By: Relevance
“…) 11. This difference may be explained by systematic hospitalization of patients under 6 weeks of age in this present study.…”
mentioning
confidence: 54%
“…) 11. This difference may be explained by systematic hospitalization of patients under 6 weeks of age in this present study.…”
mentioning
confidence: 54%
“…The peak outbreak of RSV infection is in winter and RSV is responsible for most hospitalizations in winter and spring (17). Rivera-Sepulveda et al found that most RSV related hospitalizations occurred in September through December (18). In temperate countries, RSV mostly peaks during late fall and winter, while in tropical and semi-tropical regions, RSV occurs throughout the year, especially in rainy season (19)(20)(21).…”
Section: Resultsmentioning
confidence: 99%
“…The southern US, including Florida, has a longer RSV season, sometimes starting in July [ 16 ]. In tropical regions such as the US territory of Puerto Rico and equatorial regions such as the Philippines and Mozambique, the RSV season can last year-round with minimal seasonal variations [ 17 , 18 ]. This article will review the current disease state of RSV and discuss populations at high risk of developing severe RSV.…”
Section: Introductionmentioning
confidence: 99%